Competing fundamentalisms and Egyptian women's family rights international law and the reform of Shari'a-derived legislation - Moussa, Jasmine (Brill's Arab and Islamic laws series, 2011)
The debate surrounding womens family rights under Shara-derived law has long been held captive to the competing fundamentalisms of universalism and cultural relativism. These two conflicting perspectives fail to promote practical tools through which such laws can be reformed, without prejudice to their religious nature. This book examines the development of Egypts Shara-derived family law, and its compatibility with international obligations to eliminate discrimination against women. It highlights the interplay between domestic reform processes, grounded in the tools of takhayyur, talfiq and i